Nonlinear systems and their remarkable mathematical structures - Euler, Norbert (Boca Raton, Florida : CRC Press, 2019)
"The book aims to describe some recent progress in nonlinear differential equations and nonlinear dynamical systems (both continuous and discrete)"--
Includes bibliographical references and index.
Keywords: Nonlinear theories; Differential equations, Nonlinear; Nonlinear systems